2012
DOI: 10.1007/s11046-012-9543-x
|View full text |Cite
|
Sign up to set email alerts
|

Keratinophilic Fungi Isolated from Soils of Long-Term Fold-Grazed, Degraded Pastures in National Parks of Slovakia

Abstract: A total of 939 isolates of 11 genera representing 15 species of keratinophilic fungi were isolated and identified from the soils of three long-term fold-grazed pastures in national parks of Slovakia (Pod Ploskou, Strungový príslop, and Pod Kečkou) and one non-fold-grazed pasture in sierra Stolicke vrchy (Diel) using the hair-baiting technique. Keratinophilic fungi were present in all soil samples with a prevalence of Trichophyton ajelloi and Paecilomyces lilacinus. These fungi were more abundant in soil from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The following reports confirm their world-wide distribution and occurrence in different habitats usually associated with soil environments, e.g. soil in city parks (Papini et al 1998;Vidyasagar et al 2005), flower pots (Singh et al 2009), sand in children´s sandpits (Labuda et al 2008), mud (Zaki et al 2005), poultry farms (Anbu et al 2004;Cano and Guarro 1990), marshy meadows, salt pans, desert, cultivated or uncultivated soils (Cano and Guarro 1990; Chmel and Vláčilíková 1977;Deshmukh 2004;Deshmukh et al 2008;Han et al 2013;Javorekova et al 2012;Zhang et al 2016;Zhang et al 2017) and river sediments (Ulfig et al 1997;Vidal et al 2000;Vidal et al 2002). In general, these fungi are rarely reported as animal pathogens, and in fact, only two species (C. echinulatum and C. pannicola) have been involved in mycoses (Cabanes et al 2014;Crous et al 2016).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…The following reports confirm their world-wide distribution and occurrence in different habitats usually associated with soil environments, e.g. soil in city parks (Papini et al 1998;Vidyasagar et al 2005), flower pots (Singh et al 2009), sand in children´s sandpits (Labuda et al 2008), mud (Zaki et al 2005), poultry farms (Anbu et al 2004;Cano and Guarro 1990), marshy meadows, salt pans, desert, cultivated or uncultivated soils (Cano and Guarro 1990; Chmel and Vláčilíková 1977;Deshmukh 2004;Deshmukh et al 2008;Han et al 2013;Javorekova et al 2012;Zhang et al 2016;Zhang et al 2017) and river sediments (Ulfig et al 1997;Vidal et al 2000;Vidal et al 2002). In general, these fungi are rarely reported as animal pathogens, and in fact, only two species (C. echinulatum and C. pannicola) have been involved in mycoses (Cabanes et al 2014;Crous et al 2016).…”
Section: Introductionmentioning
confidence: 52%
“…The samples were dried and stored in plastic bags in a fridge (5-8 °C) till the time of analysis (August 2015 and July 2019). Isolation of the keratinophilic fungi was done as described previously (Javorekova et al 2012). Each sample was divided into 10 subsamples.…”
Section: Sample Collection and Isolation Of The Fungimentioning
confidence: 99%
“…While A. uncinatum is also a geophilic species known to be most frequently isolated from humus-rich soils, the infrequency of this species in the current survey can be attributed to the low degree of acidity in most soils samples from Iran (pH ≥ 7). Statistically substantiated studies from Europe [ 21 , 22 , 24 , 25 ] have reported that A. uncinatum in an exceptionally acidophilic species that is less-abundantly isolated from soils with pH > 6.0. In different inquiries from Iran [ 10 , 12 , 14 ], Tunisia [ 29 ] India [ 1 , 2 , 30 ], Saudi Arabia [ 7 ], the USA [ 18 ] and Brazil [ 27 ], the dermatophytes were isolated from a wide variety of soils, especially from shady and wet places rich in organic substances, e.g., gardens, public grasslands, sludge and cultivated fields, or locations with a high animal keratin content.…”
Section: Discussionmentioning
confidence: 90%
“…While members of the N. gypsea complex were the dominant species in the soils from different localities in Iran, species other than this complex were more distinguished in the soils from some European countries. In five different reports from 1992 to 2013, T. ajelloi (currently, A. uncinatum ) was the most commonly isolated species from soils in Italy, Poland, Austria and Slovakia [ 21 , 22 , 23 , 24 , 25 ]. Such differences in species domination can be justified with differences in the types of soils sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of the keratinophilic fungi was performed as described previously (Javorekova et al 2012). Each sample was divided into 10 subsamples.…”
Section: Sample Collection and Isolation Of The Fungimentioning
confidence: 99%